A case study on the thermal-stability of polymerized small molecular acceptor-based polymer solar cells. Issue 2 (21st December 2022) - Qin, Hongmei; Ju, Shijie; Su, Wenyan; Zhao, Baofeng; Fan, Qunping; Bi, Zhaozhao; Zhang, Sen; Yu, Jifa; Lu, Guanghao; Hou, Ji-Ting; Ma, Wei; Gao, Chao; et al.
Abstract : A case study on the thermal stability of polymerized small molecular acceptor (P50-γ) based PSCs was present. And the result demonstrated the thermal-disaggregation process of polymer donor PBDB-T plays a dominant role in the degenerative efficiency. Abstract : Despite the relatively unique advantages of morphological stability in PSMA-based polymer solar cells (PSCs), the microstructure evolution of the active layer over the thermal stress is highly sensitive to the degraded efficiency still remains a challenge. To reveal the specific roles of polymer donors (PDs) and polymerized small molecular acceptors (PSMAs) in the microstructure evolution of active layers over thermal stress, we developed a new PSMA named P50-γ using near-infrared absorption via a random ternary copolymerization strategy of combining two different small molecule precursors with BPT-core and BPTz-core. The resultant PSMA-based PSCs have achieved a high-power conversion efficiency (PCE) of 15.1% when paired with the commonly used PD (PBDB-T). Furthermore, we reveal the respective influences of PD and PSMA in the active layer on the thermal stability of devices. Specifically, after the thermal annealing treatment at 80 °C for 150 hours, PSC maintained ∼80% of the initial PCE, in which the photocurrent was slightly decreased while the fill factor (FF) significantly reduced. Systematical studies indicate that the decrease of PCE over thermal stress is mainly attributed to the burn-in disaggregation of PD, which is supported by the absorption spectra and crystalline characteristics of the annealed active layer. Our work not only presents a new PSMA to achieve efficient and relatively stable PSCs but also reveals for the first time that PD dominates the thermal-disaggregation process of PSMA-based PSCs.